Titanium porous body, and method for producing titanium porous body
A method using small particle size titanium powder, alcohol solvent, and coal tar naphtha dispersant produces a titanium porous body with fine pores, addressing membrane damage and maintaining permeability in PEM electrolyzers.
Patent Information
- Application Number
- JP2024172739
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-01
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Titanium porous bodies used in PEM type water electrolyzers risk damaging the electrolyte membrane due to large pores allowing the membrane to deform and penetrate, and existing production methods can lead to titanium powder agglomeration resulting in uneven pore sizes.
A method involving the use of titanium powder with a small particle size, an organic solvent (alcohol) and a dispersant containing coal tar naphtha to create a paste that is dried and sintered, preventing agglomeration and forming a titanium porous body with a large number of fine pores on the surface.
The resulting titanium porous body has a smooth surface with numerous fine pores, reducing the risk of electrolyte membrane damage and maintaining high air and liquid permeability, suitable for use in PEM type water electrolysis devices.
Smart Images

Figure 2024178463000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous titanium body and a method for producing a porous titanium body. [Background technology]
[0002] Porous titanium produced by sintering titanium powder or the like has air and liquid permeability due to its fine pores, and electrical conductivity. It also has high corrosion resistance due to the formation of a passive film on the surface.
[0003] Porous titanium with such properties is being considered for use in porous transport layers (PTLs) in polymer electrolyte membrane (PEM)-type water electrolysis equipment, which are in environments where corrosion may occur. In particular, hydrogen produced in PEM-type water electrolysis equipment using electricity derived from renewable energy is called "green hydrogen," and is attracting great expectations in recent years as the movement toward a decarbonized society accelerates.
[0004] As a related technique, Patent Document 1 proposes, for the purpose of "providing a titanium porous plate that can be in sufficient contact with adjacent members and that allows fluids such as liquids and gases to flow and diffuse well, and a water electrolysis electrode and water electrolysis apparatus made of this titanium porous plate," proposing "a titanium porous plate made of a sintered body of titanium or a titanium alloy, the titanium porous plate having a three-dimensional mesh structure with communicating pores that open on the surface of the titanium porous plate and communicate with internal pores, the opening rate in one main surface being smaller than the opening rate in the other main surface, and the difference between the opening rate in the one main surface and the opening rate in the other main surface being 10% or more." In the "titanium-containing slurry formation process" during the manufacture of this "titanium porous plate," it is described that "the raw material powder is mixed with a water-soluble resin binder (methyl cellulose), an organic solvent (neopentane, hexane and butane), a plasticizer (glycerin and ethylene glycol), water as a solvent, a foaming agent, and in some cases a surfactant (alkylbenzene sulfonate) to produce a titanium-containing slurry."
[0005] Furthermore, Patent Document 2 discloses, for the same purpose as above, "a titanium porous plate made of a sintered body of titanium or a titanium alloy, the titanium porous plate having a three-dimensional mesh structure with communicating pores that open on the surface of the titanium porous plate and communicate with internal pores, the titanium porous plate having a structure in which a first layer and a second layer are laminated in the thickness direction, the average pore diameter of the second layer being larger than the average pore diameter of the first layer." In Patent Document 2, to manufacture such a "titanium porous plate material", a "first titanium-containing slurry" is used in which "raw material powder is mixed with a water-soluble resin binder (methylcellulose), an organic solvent (neopentane, hexane and butane), a plasticizer (glycerin and ethylene glycol), water as a solvent, and in some cases a surfactant (alkylbenzene sulfonate)", and a "second titanium-containing slurry" is used in which "raw material powder is mixed with a water-soluble resin binder (methylcellulose), an organic solvent (neopentane, hexane and butane), a plasticizer (glycerin and ethylene glycol), water as a solvent, and in some cases a surfactant (alkylbenzene sulfonate), as well as a foaming agent". [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2022 / 210421 [Patent Document 2] International Publication No. 2022 / 210681 Summary of the Invention [Problem to be solved by the invention]
[0007] When a porous titanium body is used as a porous transport layer in a PEM-type water electrolysis device, the porous titanium body may be pressed against the electrolyte membrane when it is assembled. If the pores in the porous titanium body are large, the electrolyte membrane pressed against the porous titanium body may partially enter the pores, causing significant deformation in the areas close to the pores, which may damage the electrolyte membrane.
[0008] Therefore, in order to prevent damage to the electrolyte membrane, it is desirable for the titanium porous body to have small pores that open to the surface facing the electrolyte membrane, and for a large number of such pores to be present on that surface. A titanium porous body with a large number of pores is less likely to cause damage to the electrolyte membrane as described above, and can serve as a porous transport layer with good air and liquid permeability.
[0009] In the techniques described in Patent Documents 1 and 2, it is believed that the titanium powder in the paste may aggregate during the production of the titanium porous body. If the titanium powder aggregates in the paste, the resulting bias in the titanium powder may result in the formation of large pores on the surface of the titanium porous body after production.
[0010] An object of the present invention is to provide a porous titanium body having a surface on which a relatively large number of fine pores are formed, and a method for producing the porous titanium body. [Means for solving the problem]
[0011] As a result of intensive research, the inventors have found that by mixing titanium powder with a relatively small particle size to form a paste containing no water but an organic solvent alcohol, and by using a paste containing a dispersant containing coal tar naphtha, after drying, debinding and sintering the paste, a titanium porous body having a large number of fine pores formed on the surface can be obtained. This is believed to be because the specific dispersant effectively suppresses the aggregation or uneven distribution of the titanium powder in the paste.
[0012] The porous titanium body of the present invention is a sheet-like body having pores, and the average area of the pores open to at least one surface of the body is 10 μm 2 More than 17μm 2 The standard deviation of the area of the pores is 20 μm or less. 2 The area is 40000μm or less. 2The number of the pores present within a rectangular region having an aspect ratio of 4:5 is 250 or more.
[0013] The thickness of the porous titanium body is preferably 40 μm or more and 500 μm or less.
[0014] The surface of the titanium porous body has a pore area of 10 μm 2 More than 14μm 2 It is preferable that:
[0015] The surface of the titanium porous body has a standard deviation of the area of the pores of 17 μm 2 It is preferable that:
[0016] The surface of the titanium porous body has an area of 40,000 μm 2 It is preferable that the number of pores present in a rectangular region having an aspect ratio of 4:5 is 300 or more.
[0017] The method for producing a porous titanium body of this invention is a method for producing a sheet-like porous titanium body having pores, and includes the following steps: a drying step in which a paste containing titanium powder having an average particle size of 25 μm or less, an organic binder, and an organic solvent, but no water as a solvent, is dried to obtain a sheet-like molded body; a binder removal step in which the molded body is heated to volatilize the organic binder; and a sintering step in which the molded body after the binder removal step is heated to sinter the titanium powder, wherein the organic solvent in the paste is alcohol, and the paste contains a dispersant containing coal tar naphtha.
[0018] In the above manufacturing method, the content of the dispersant in the paste is preferably 0.01% by mass or more and 0.3% by mass or less.
[0019] The above manufacturing method makes it possible to manufacture a porous titanium body having a thickness of 40 μm or more and 500 μm or less. Effect of the Invention
[0020] The porous titanium body of the present invention has a surface on which a relatively large number of fine pores are formed, and the method for producing a porous titanium body of the present invention is suitable for producing such a porous titanium body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, an embodiment of the present invention will be described in detail. The porous titanium body according to one embodiment of the present invention is in the form of a sheet having pores. When the area and number of pores opening to at least one surface of the porous titanium body are checked, the average area of the pores is 10 μm 2 More than 17μm 2 The standard deviation of the area of the pores is 20 μm or less. 2 The area is 40000μm or less. 2 The number of the pores present within a rectangular region having an aspect ratio of 4:5 is 250 or more.
[0022] In this way, if a relatively large number of relatively fine pores are formed on at least one surface of the titanium porous body, it is believed that when the titanium porous body is used as a porous transport layer of a PEM water electrolysis device, damage to the electrolyte membrane pressed against the surface is effectively suppressed. This is because the pores opening on the surface are fine, making it difficult for the electrolyte membrane to partially enter into the pores, and if there are a large number of pores, the load acting on the electrolyte membrane due to the titanium porous body being pressed against it is dispersed. Therefore, it can be said that this titanium porous body can be suitably used as a porous transport layer of a PEM water electrolysis device.
[0023] To manufacture the titanium porous body, a method can be adopted in which, although not limited thereto, a paste containing titanium powder, an organic binder, and an organic solvent is dried, the binder is removed, and the titanium powder is sintered in sequence. The organic solvent of the paste is alcohol, and the paste does not contain water as a solvent. In such a manufacturing method, it is particularly important to use titanium powder of a predetermined small particle size and to make the paste contain a dispersant containing coal tar naphtha. It is considered that a small amount of coal tar naphtha in the dispersant adheres to the surface of the titanium powder, making the particles of the titanium powder slide easily against each other, and acts to disperse the titanium powder in the paste well. This suppresses the aggregation or bias of the titanium powder in the paste, and the titanium powder having a small particle size can be bonded in a relatively uniform arrangement during sintering. As a result, a titanium porous body having a large number of fine pores formed on at least one surface is obtained. Typically, a large number of fine pores are often formed on the surface behind the above-mentioned surface of the titanium porous body.
[0024] (composition) The titanium porous body is made of titanium. If it is made of titanium, a titanium porous body having high electrical conductivity at a certain relative density can be obtained. The titanium content of the titanium porous body is preferably 97% by mass or more, and more preferably 98% by mass or more. The upper limit of the titanium content is not limited to this, but may be, for example, 99.8% by mass or less, or 99% by mass or less. This titanium content means the purity of titanium taking into account not only metal components but also impurities of gas components such as oxygen. Therefore, the titanium content can be calculated by subtracting the total content of impurities including metal components and gas components from 100% by mass.
[0025] The titanium porous body may contain Fe as an impurity, and the Fe content may be, for example, 0.25 mass% or less. The titanium porous body may also contain Ni, Cr, Al, Cu, Zn, and Sn as unavoidable impurities resulting from the manufacturing process. It is preferable that each of the contents of Ni, Cr, Al, Cu, Zn, and Sn is less than 0.10 mass%, and that the total content of these elements is less than 0.30 mass%.
[0026] The oxygen content of the titanium porous body is not particularly limited, but may be 0.9 mass % or more and 2.0 mass % or less. The oxygen content can be measured by inert gas fusion-infrared absorption method.
[0027] The titanium porous body may have a purity equivalent to pure titanium class 1 to 4, typically class 1 or 2, of JIS H 4600 (2012), excluding the oxygen content.
[0028] (Sheet size) The thickness of the sheet-like titanium porous body may be 40 μm or more and 500 μm or less. For example, a porous transport layer of a PEM water electrolysis device may require such a relatively thick titanium porous body. On the other hand, if the thickness is too large, the PEM water electrolysis device may become large. The thickness of the titanium porous body may be, for example, 400 μm or less, 350 μm or less, 300 μm or less, 250 μm or less, or 200 μm or less, while it may be 40 μm or more, or 80 μm or more.
[0029] The thickness is measured at five points in total, four points on the periphery and one point in the center of the titanium porous body, using a digital thickness gauge with a flat gauge having a Φ10 mm probe and a measurement accuracy of 0.001 to 0.01 mm, such as a Mitutoyo digital thickness gauge (model number 547-321), and the average of these measured values is used. When the sheet-like titanium porous body is rectangular in plan view, the four peripheral points are the four corners.
[0030] The surface area of the sheet-like porous titanium body in plan view is not particularly limited and may be appropriately determined depending on the application. For example, 2 More than 350000mm 2 Below, 40000mm 2 ~600000mm 2 This may happen.
[0031] The term "sheet-like" for the titanium porous body means a plate or foil shape having a thickness smaller than the dimensions in a plan view, and there is no restriction on the shape in a plan view.
[0032] (pore) The titanium porous body is composed of titanium powder particles bonded together, and has a three-dimensional mesh structure in which pores are formed between the titanium powder particles bonded together. As an example, the titanium porous body may have a skeleton with a three-dimensional mesh structure like titanium sponge. Note that titanium porous bodies manufactured using titanium fibers tend to have a three-dimensional mesh structure like nonwoven fabric. In many cases, the inside of the skeleton of the titanium porous body, which is composed of titanium powder particles bonded together, is solid, not hollow.
[0033] Among the pores formed in the titanium porous body, the average area of a large number of pores that are open to at least one surface of the titanium porous body is 10 μm 2 More than 17μm 2 The standard deviation of the surface pore area is 20 μm 2 In this way, if the majority of the pores on at least one surface have a relatively small area, the surface can be said to be generally smooth, and damage to the electrolyte membrane in a PEM water electrolysis device can be effectively suppressed. From this perspective, the average area of the pores on the surface is set to 10 μm 2 More than 14μm 2 From the same viewpoint, it is preferable that the standard deviation of the area of the pores on the surface is 17 μm or less. 2It is preferable that the average pore area is less than 100 mm. If the average pore area is too small, the air permeability or liquid permeability may decrease. However, it is acceptable that a small number of pores having a relatively large area are present on the surface.
[0034] In addition, the surface area is 40,000 μm 2 The number of pores present in a rectangular region having an aspect ratio of 4:5 is 250 or more, preferably 300 or more. The presence of many fine pores on the surface as described above makes it easier to ensure the required air permeability or liquid permeability, and can also achieve a smooth surface. The number of pores in the rectangular region is not limited to this, but may be, for example, 500 or less.
[0035] The average value and standard deviation of the area of the pores opening to the surface as well as the number of pores in a given rectangular region are measured using a scanning electron microscope (Keyence Ultra-Deep Multi-Angle Lens VHX-D510). 2 A SEM image is obtained at a magnification of 1500 times for a rectangular region with an aspect ratio of 4:5. Then, the SEM image is analyzed using a scanning electron microscope, and a half value of the maximum brightness detection value for the SEM image is set as a threshold value, and a closed region with a brightness in the range of 0 to the threshold value is regarded as one pore. At this time, if necessary, a binarization process may be performed on the SEM image. After the binarization process, a small grain removal process of 50 pixels or less (processing of black pixels after binarization) is performed, and then a filling process of 50 pixels or less (processing of white pixels after binarization) is performed. Using this, the number and area of each pore are calculated, and a standard deviation value is obtained as the square root of the variance. Such an analysis of the SEM image is performed for five rectangular regions on the surface of the titanium porous body, at least a part of which is shifted from each other, and the average value of the area, the standard deviation value, and the average of the number of pores in those rectangular regions are respectively the average value and standard deviation value of the area of the pores of the titanium porous body and the number in the rectangular regions. In the case of a titanium porous body that is a square or rectangular shape in plan view, the above-mentioned five rectangular regions are the five rectangular regions at the center and the four corners.
[0036] (Application) The titanium porous body can be particularly suitably used for the porous transport layer of a PEM type water electrolysis device. The PEM type water electrolysis device may include an anode and a cathode, an electrolyte membrane such as a perfluorocarbon sulfonic acid membrane disposed between the anode and the cathode and having electrode catalyst layers of a platinum group metal or the like provided on both sides, and a porous transport layer disposed between each electrode catalyst layer of the electrolyte membrane and the anode or the cathode.
[0037] In the above PEM water electrolysis device, when water is supplied to the anode and a voltage is applied, the water moves through the porous transport layer on the anode side and reaches the electrode catalyst layer, where it is decomposed into oxygen and protons (H + The protons move from the anode to the cathode through the electrolyte membrane on the anode side, obtain electrons at the electrode catalyst layer on the cathode side, and generate hydrogen on the cathode side. Meanwhile, oxygen moves through the porous transport layer to the discharge flow path and is discharged outside the device.
[0038] In such a PEM-type water electrolysis device, the space in which the porous transport layer is disposed, particularly on the anode side, is subject to strong acidic and strong oxidizing conditions, but a titanium porous body having high corrosion resistance can be used satisfactorily as a porous transport layer in such an extremely severe environment. Furthermore, as described above, in the titanium porous body of the present invention, a large number of fine pores are formed on at least one surface, and therefore, when the titanium porous body is disposed in a PEM-type water electrolysis device with its surface side pressed against the electrolyte membrane, damage to the electrolyte membrane can be suppressed.
[0039] In addition to the PEM-type water electrolysis devices mentioned above, the use of titanium porous bodies is also being considered for organic electrolysis synthesis using PEM-type reactors. In such devices, electrolysis is carried out by passing protons through a proton exchange membrane. The titanium porous bodies described here may also be well suited for organic electrolysis synthesis using PEM-type reactors, and are considered to be usable as a porous transport layer (PTL) on the anode side of electrolysis devices that use proton exchange membranes.
[0040] (Manufacturing method) The above-mentioned titanium porous body can be manufactured, for example, by carrying out the following steps in this order: paste preparation, paste application, drying, binder removal, and sintering. However, if the paste has already been prepared and obtained, or if the paste has been applied in sheet form, the paste preparation and paste application steps may be omitted.
[0041] First, in a paste preparation step, a paste containing titanium powder, an organic binder, and an organic solvent is prepared.
[0042] Here, the average particle size of the titanium powder contained in the paste can be 25 μm or less, preferably 18 μm or less. By using titanium powder with such a small particle size and further using a predetermined dispersant as described below, the surface of the titanium porous body finally produced can be smoothed. If the average particle size of the titanium powder exceeds 25 μm, the pores on the surface of the titanium porous body tend to become large even if a predetermined dispersant is used. In addition, from the viewpoint of suppressing an increase in manufacturing costs by using relatively inexpensive titanium powder and facilitating the handling of the titanium powder, the average particle size of the titanium powder may be 5 μm or more, or even 10 μm or more. The average particle size means the particle size at which the cumulative distribution on a volume basis is 50% in the particle size distribution obtained by the laser diffraction scattering method.
[0043] The titanium powder is preferably one with high purity, and pure titanium powder can be used. The titanium powder may have a titanium content of 99% by mass or more. The titanium powder may be a crushed powder, a spherical powder such as atomized powder, or any other powder. Titanium hydrogen powder obtained by hydrogenating and crushing a titanium raw material such as sponge titanium can also be used as the titanium powder. In this case, the hydrogen content of the titanium hydrogen powder is preferably 5% by mass or less. In addition, when using titanium hydrogen powder, dehydrogenation treatment may be performed in a temperature range of 500°C or more and 650°C or less in a reduced pressure atmosphere such as vacuum between the binder removal step and the sintering step described below. Hydrogenated and dehydrogenated titanium powder (HDH powder) obtained by dehydrogenating titanium powder can also be used.
[0044] In addition, various organic binders can be appropriately selected and used for the paste, and examples of such organic binders include methyl cellulose, polyvinyl alcohol, ethyl cellulose, acrylic, and polyvinyl butyral. Organic binders that exhibit hydrophobicity are preferable. However, they are not limited to those listed here. The organic solvent is alcohol (ethanol, isopropanol, terpineol, butyl carbitol, etc.). As an example, the organic binder may be polyvinyl butyral and the organic solvent may be isopropyl alcohol. The paste may further contain a plasticizer (glycerin, ethylene glycol, etc.) and a surfactant (alkylbenzene sulfonate, etc.).
[0045] The paste does not contain water as a solvent. It is preferable that the paste does not further contain a foaming agent. This is to suppress the aggregation of titanium powder in the paste due to the difference in drying behavior between the organic solvent and water during drying when the paste contains water, and the occurrence of pinholes on the surface of the titanium porous body. Furthermore, when the paste does not contain a foaming agent, large local voids due to foaming of the foaming agent are not formed in the titanium porous body. As a result, the titanium porous body is likely to have a smooth surface and is less likely to crack during handling. Therefore, a foaming process that generates bubbles in the paste is not performed here. It is sufficient that the paste does not contain water as a solvent, and the inclusion of water that may be unintentionally mixed into the paste due to moisture absorption or the like is permitted.
[0046] The paste also contains a dispersant containing coal tar naphtha. The use of such a dispersant is believed to disperse the titanium powder in the water-free paste, suppressing its aggregation or uneven distribution, and thus suppressing the formation of large pores on the surface of the titanium porous body. In addition, coal tar naphtha is a hydrocarbon mixture with a relatively low boiling point, and is believed to volatilize together with the organic solvent and organic binder during the drying and binder removal processes, so it does not have a significant effect on the titanium porous body.
[0047] In particular, when the dispersant contains 20% by mass or more of coal tar naphtha, the dispersing effect of the titanium powder can be more effectively exerted. The dispersant may contain components other than coal tar naphtha, and may typically contain a polycarboxylic acid amine salt. In order to disperse the titanium powder more satisfactorily, the content of the dispersant in the paste is preferably 0.01% by mass or more and 0.3% by mass or less, more preferably 0.01% by mass or more and 0.1% by mass or less, particularly preferably 0.05% by mass or more and 0.1% by mass or less.
[0048] The paste can be prepared by mixing the titanium powder, organic binder, organic solvent, and the like as described above, using, for example, a mixer with an agitator, a rotary mixer, a triple roll mill, etc. At this time, the mixture may be pulverized using a vibration mill, a bead mill, or other pulverizing mixer, etc.
[0049] In the paste application step, the paste is applied relatively thinly onto the substrate. A release layer may be provided on the substrate in advance. In this case, the paste is applied onto the substrate via the release layer. When a release layer is provided on the substrate, it becomes easier to separate the molded body obtained by drying the paste from the substrate after the drying step.
[0050] As the substrate, a resin substrate is preferable because it is relatively inexpensive. In addition, the resin substrate has the advantage that it is easy to handle because it has flexibility. Specific materials for the resin substrate include, for example, polyesters such as PET (polyethylene terephthalate) and PEN (polyethylene naphthalate), and polyvinyls such as polyethylene, polypropylene, polystyrene, and polyvinyl alcohol. Among them, PET is preferable because it is inexpensive and the molded body can be easily separated from the substrate after the drying process.
[0051] It is optional to provide a release layer on the substrate, but when a release layer is provided, a silicone coating or the like can be used as the release layer. For example, a release layer can be provided on the substrate by selecting a substrate on which such a material has been applied in advance, such as Therapeel (registered trademark) manufactured by Toray Industries, Inc. By providing a release layer on the substrate, it becomes possible to easily separate the thin sheet-like molded body obtained after the drying process from the substrate.
[0052] In the drying step, the paste is dried on the substrate in, for example, an oven or a dryer, etc. This causes the organic solvent in the paste to evaporate, and a sheet-like molded body is obtained on the substrate.
[0053] The drying temperature can be 90° C. or higher and 165° C. or lower. By heating and drying the paste at a temperature within this range, it is possible to complete the drying in a relatively short time while suppressing boiling of the organic solvent and other components in the paste. As a result, localized surface roughness and the formation of pinholes caused by boiling of the organic solvent components and long-term heating are suppressed, making it easier to obtain a titanium porous body with a smooth surface.
[0054] The drying time is not particularly limited and may be appropriately determined, and may be, for example, 5 minutes or more and 300 minutes or less. From the viewpoint of effectively removing the organic solvent from the paste, it is desirable to perform the drying while discharging gas from the inside of the furnace or dryer. When discharging gas from the inside of the furnace or dryer, the inside of the furnace or dryer may be made into a reduced pressure atmosphere, or the pressure may be made the same as the outside pressure by supplying a gas such as the atmosphere.
[0055] When the drying step is completed, the molded body obtained by drying the paste may be separated from the substrate, for example by peeling it off, before the binder removal step. If the molded body is separated from the substrate at this stage, it is possible to suppress the deterioration of the sheet shape of the titanium porous body due to deformation of the substrate when the subsequent binder removal step or sintering step is performed together with the substrate, and the contamination of the titanium porous body due to the material of the substrate. When a resin substrate is used, it becomes easy to separate the molded body from the substrate. In the case of a metal substrate, it may be difficult to separate the molded body from the substrate.
[0056] Next, in the binder removal step, the molded body is heated in a furnace to volatilize and remove the organic binder in the molded body. In the binder removal step, for example, the molded body can be heated to a temperature of 300° C. or more and 450° C. or less for a time period of 3 hours or more and 12 hours or less.
[0057] Thereafter, the molded body that has been subjected to the binder removal process is subjected to a sintering process to sinter the titanium powder in the molded body. The conditions for the sintering process are not particularly limited as long as the titanium powder in the molded body is sintered. For example, in the sintering process, the molded body may be heated to a temperature of 700°C or more and 1000°C or less for a period of 1 hour or more and 4 hours or less. Since the titanium porous body of this embodiment is relatively thin, the titanium powder can be appropriately sintered by heating at a relatively low temperature for a short period of time. The sintering atmosphere may be, for example, 1.0×10 -2 The atmosphere may be a vacuum of less than Pa or an inert atmosphere of Ar or He.
[0058] After the sintering step, a porous titanium body is obtained, which, as described above, has a large number of fine pores formed on at least one surface. EXAMPLES
[0059] Next, a titanium porous body according to the present invention was produced as a prototype and its effects were confirmed, which will be described below, however, the description here is merely for illustrative purposes and is not intended to be limiting.
[0060] A paste was prepared by mixing titanium powder (HDH powder) having an average particle size shown in Table 1 and a titanium content of 99% by mass or more with polyvinyl butyral as an organic binder and isopropyl alcohol as an organic solvent. The paste did not contain a foaming agent.
[0061] In Examples 1 to 7 and Comparative Examples 2 and 4, the paste further contained a dispersant A. Dispersant A was SN Sparce 2190 manufactured by San Nopco Ltd., which contained 42 mass % of coal tar naphtha and 58 mass % of polycarboxylate amine salts, etc.
[0062] A paste containing no dispersant was used in Comparative Example 1. A paste containing Dispersant B was used in Comparative Example 3. Dispersant B was SN Sparce 70 manufactured by San Nopco Ltd., which contains 63 mass% of an aliphatic amide surfactant, 26 mass% of a nonionic surfactant, and 11 mass% of diethanolamine.
[0063] The mass ratio of titanium powder:organic binder:organic solvent was 100:9:36 in all of Examples 1 to 7 and Comparative Examples 1 to 3. The contents of the dispersant in the pastes of Examples 1 to 7 and Comparative Examples 2 to 4 are shown in Table 1.
[0064] The pastes of Examples 1 to 7 and Comparative Examples 1 to 3 did not contain water, but in Comparative Example 4, the organic solvent was reduced by 10 mass% from the paste of Example 1 and 10 mass% water was added instead.
[0065] For each of Examples 1 to 7 and Comparative Examples 1 to 3, the above paste was applied in the form of a sheet onto a release layer provided on a PET sheet, which was then heated and dried in an air atmosphere at the temperatures shown in Table 1 to remove the organic solvent, thereby obtaining a molded article. Next, the molded article was peeled off from the release layer and heated at 360°C in an air atmosphere to carry out a binder removal treatment. Thereafter, the molded article was dried in a vacuum atmosphere (1.0 x 10 -3 The titanium powder is sintered at 775°C under low pressure (less than 1 Pa) to produce a surface area of 240,000 mm 2 A sheet-like porous titanium body having a planar dimension of about 600 mm × 400 mm was produced. In Comparative Example 4, the titanium powder in the paste was not dispersed but aggregated, so the steps after coating on the PET sheet were not carried out and the production of the porous titanium body was abandoned.
[0066] For each of the titanium porous bodies produced as described above, the thickness, the average value and standard deviation of the area of the pores on the surface that was in contact with the release layer of the PET sheet during production, and the number of pores in a rectangular region were measured by the method described above. Here, the titanium porous body was cut into five pieces, and each sample was observed using a scanning electron microscope. As the scanning electron microscope, a Keyence ultra-deep multi-angle lens VHX-D510 was used. The results are shown in Table 1. Note that the titanium porous bodies of all the examples had a titanium content of 97% by mass or more and an oxygen content of 0.9% by mass or more and 2.0% by mass or less.
[0067] [Table 1]
[0068] As can be seen from Table 1, all of the titanium porous bodies of Examples 1 to 7 had surfaces on which numerous fine pores were formed.
[0069] In contrast, in Comparative Example 1, since no dispersant was added to the paste during production, the standard deviation of the pore area on the surface of the titanium porous body was large and the number of pores was small. In Comparative Example 2, since the average particle size of the titanium powder used in production was large, the average value and standard deviation of the pore area on the surface of the titanium porous body were both large and the number of pores was small. In Comparative Example 3, since the dispersant B added to the paste did not contain coal tar naphtha, the average value and standard deviation of the pore area on the surface of the titanium porous body were large and the number of pores was small.
[0070] In addition, to confirm the air permeability of each titanium porous body, the air permeability of each titanium porous body was measured using a Gurley densometer in accordance with ISO-5636. However, the size of the vent hole in the air permeability measurement was 6 mm instead of 22 mm.
[0071] Air permeability depends on the thickness of the titanium porous body, and the titanium porous body of Example 1 having a thickness of 500 μm had an air permeability of 5 μm / Pa·S or more. The titanium porous bodies of Examples 2, 4, 6 and 7 having a thickness of 100 μm had an air permeability of 50 μm / Pa·S or more. The titanium porous body of Example 3 having a thickness of 40 μm had an air permeability of 100 μm / Pa·S or more. The titanium porous body of Example 5 having a thickness of 250 μm had an air permeability of 10 μm / Pa·S or more. All of Examples 1 to 7 had excellent air permeability according to their respective thicknesses.
[0072] From the above, it has been found that according to the present invention, a porous titanium body having a surface on which a comparatively large number of fine pores are formed can be obtained.
Claims
1. A sheet-shaped porous titanium body having pores, At least one of the surfaces has an average area of pores that open to the surface of 10 μm 2 More than 17 μm 2 The standard deviation of the area of the pores is 20 μm or less. 2 and the area is 40,000 μm 2 The titanium porous body has a rectangular region having an aspect ratio of 4:5 and the number of the pores present therein is 250 or more.
2. 2. The titanium porous body according to claim 1, which has a thickness of 40 μm or more and 500 μm or less.
3. On the surface, the average area of the pores is 10 μm 2 More than 14 μm 2 3. The titanium porous body according to claim 1 or 2, wherein:
4. On the surface, the standard deviation of the area of the pores is 17 μm 2 3. The titanium porous body according to claim 1 or 2, wherein:
5. On the surface, an area of 40,000 μm 2 3. The titanium porous body according to claim 1, wherein the number of pores present within a rectangular region having an aspect ratio of 4:5 is 300 or more.
6. A method for producing a sheet-shaped porous titanium body having pores, comprising the steps of: a drying step of drying a paste containing titanium powder having an average particle size of 25 μm or less, an organic binder, and an organic solvent, but not containing water as a solvent, to obtain a sheet-like molded body; a binder removal step of heating the molded body to volatilize the organic binder; a sintering step of heating the molded body after the binder removal step to sinter the titanium powder; having A method for producing a titanium porous body, comprising the steps of: using an alcohol as the organic solvent in the paste; and adding a dispersant containing coal tar naphtha to the paste.
7. 7. The method for producing a porous titanium body according to claim 6, wherein the content of the dispersant in the paste is 0.01% by mass or more and 0.3% by mass or less.
8. The method for producing a porous titanium body according to claim 6 or 7, which produces a porous titanium body having a thickness of 40 µm or more and 500 µm or less.
Citation Information
Patent Citations
Titanium porous plate, electrode for water electrolysis, and water electrolysis device
WO2022210421A1
Titanium porous plate material, electrode for water electrolysis, and water electrolysis device
WO2022210681A1
